Virtual Touch Tissue Imaging for Differential Diagnosis of Thyroid Nodules: Additional Value of the Area Ratio. (28th March 2016) - Xu, Jun-Mei; Xu, Hui-Xiong; Zhang, Yi-Feng; Guo, Le-Hang; Liu, Lin-Na; Bo, Xiao-Wan; Xu, Xiao-Hong
Abstract : Objectives: To evaluate the additional value of the area ratio on Virtual Touch tissue imaging (VTI; Siemens Medical Solutions, Mountain View, CA) for diagnosis of thyroid nodules referred to surgery. Methods: From April 2013 to February 2014, 205 consecutive patients with 225 histologically proven thyroid nodules were enrolled in this retrospective study. Virtual Touch tissue imaging and area ratio measurements were performed for each nodule. The area ratio was defined as the area of the nodule on VTI divided by the area on B‐mode sonography. Nodule stiffness on VTI was graded from I (soft) to VI (hard). Receiver operating characteristic curve analyses of VTI, area ratio, and the combination of VTI and area ratio were performed. The sensitivity, specificity, accuracy, positive predictive value (PPV), negative predictive value (NPV), and Youden index were also evaluated. Results: By receiver operating characteristic curve analyses, the cutoff values were VTI grade IV and area ratio of 1.09, respectively. Nodules with VTI grade IV or higher or area ratio of 1.09 or higher were more likely to be malignant. The sensitivity, specificity, accuracy, PPV, NPV, and Youden index were 78.6%, 92.3%, 88.0%, 82.1%, 90.5%, and 0.709 for VTI and 81.4%, 87.1%, 85.3%, 74.0%, 91.2%, and 0.685 for area ratio (all P > .05). However, when using the criterion of VTI grade IV or higher and area ratio of 1.09 or higher as a combination, the sensitivity, specificity, accuracy, PPV, NPV, and Youden index increased to 94.3%, 97.4%, 96.4%, 94.3%, 97.4%, and 0.917 (all P < .05 compared to VTI or area ratio alone, except for specificity between VTI and the combination). Conclusions: The diagnostic performance of VTI grading and the area ratio for differentiation between benign and malignant thyroid nodules is equivalent. The performance is further improved with a combination of VTI grading and area ratio analysis.